2018
DOI: 10.1039/c8py00492g
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a conventional polyurethane composition provides significant anti-biofilm activity against Escherichia coli

Abstract: Tecoflex-NH3+ exhibited a contact-killing mechanism and showed excellent anti-biofilm properties against E. coli even after 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…After 72 h of experiments, the worms’ viability showed a ratio of 50/50 with minimal activity (scale 1) and death (scale 0) for the loaded PU matrices with 0.5 and 1.0 wt% curcumin (Table 1). The literature has reported the influence of cationic groups that provide significant antimicrobial/antifungal activities . Peng et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 72 h of experiments, the worms’ viability showed a ratio of 50/50 with minimal activity (scale 1) and death (scale 0) for the loaded PU matrices with 0.5 and 1.0 wt% curcumin (Table 1). The literature has reported the influence of cationic groups that provide significant antimicrobial/antifungal activities . Peng et al .…”
Section: Resultsmentioning
confidence: 99%
“…The literature has reported the influence of cationic groups that provide significant antimicrobial/antifungal activities . Peng et al . prepared an amine‐functionalized polyurethane based on a commercial material named Tecloflex®.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the antimicrobial activity, the synthesized Ag NPs were tested for bactericidal activity against E. coli [14]. A single colony of E. coli was grown overnight at 37°C in LB medium on an orbital shaker at 150 rpm.…”
Section: Antimicrobial Activity Studiesmentioning
confidence: 99%
“…Another study by Li et al showed that cationic monomer, methacryloxylethylcetyl dimethyl ammonium chloride (DMAE-CB) was also effective in the removal of a biofilm of S. mutans , the common bacteria associated dental problems [ 164 ]. Peng et al modified the polyurethane compound, the main compound for catheter by copolymerization of an amine functionalized N-substituted diol to give a cationic polyurethane (Tecoflex-NH3), and showed that the cationic polyurethane shown contact killing of E. coli and prevent build-up of biofilm on the surfaces, thus, reducing the chances of CAUTI, one of the main causes of the nosocomial infections [ 165 ]. Another example of an antimicrobial polymer is Polyhexamethlene biguanide (PHMB), a cationic polymer that has been used in the clinic for over than 40 years with no sign of bacterial resistance [ 166 ].…”
Section: Promising Novel Therapies For Prevention and Treatment Ofmentioning
confidence: 99%